The Influence of Brand Personality, Celebrity Endorser, and Religiosity on Muslim Clothing Consumer Behavior - Sharfina Lubis; Dias Satria (Islamic Economics and finance in Focus, 2025)
The Muslim fashion industry is undergoing rapid growth and diversification worldwide, including in Indonesia, where the majority of the population adheres to Islamic principles in terms of personal appearance. The pervasive access to information regarding lifestyles and prevailing trends has led to a societal phenomenon in which millennials feel compelled to emulate the behaviors and lifestyles espoused on social media platforms in order to gain acceptance within their social circles. This perspective stands in contrast to the established principles of Islamic consumption. The role of religiosity in shaping individual preferences and perceptions of brand personality during the consumption process merits further investigation. In the context of purchasing decisions, consumers may experience uncertainty regarding their own preferences or be susceptible to the influence of groups or individuals they believe within the relevant field. The present study employs a quantitative research approach, using an explanatory method. The data analysis method employed in this study utilizes multivariate testing techniques in conjunction with the Structural Equation Modeling (SEM) movement towards Partial Least Square (PLS). The objective of this research is to examine and understand the factors that influence consumer purchasing decisions. It is imperative to acknowledge that consumers possess distinct needs, preferences, and satisfaction levels.